THE INFLUENCE OF SERVICE QUALITY, PRODUCT COMPLETENESS, AND CONSUMER TRUST ON CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY IN EVAN MOTOR WORKSHOPS - Rahayu Lestari; Anisah Julia; Kumba Digdowisesiso (Jurnal Ekonomi, 2022)
This study aims to analyze the effect of service quality, product completeness, and consumer trust on customer satisfaction and the impact on customer loyalty at Evan Motor Workshop. Sources and research data were collected using primary data in the form of a questionnaire, and the research data was given to 100 respondents. The research sample was taken using purposive sampling. The analytical method used is partial least squares (PLS) with the help of the SmartPLS 3.0 application.The results of the study partially found that there was a negative and insignificant effect of product completeness on customer satisfaction at the Evan Motor Workshop; there was a negative and insignificant effect of product completeness on customer loyalty at the Evan Motor Workshop; there was a positive and significant effect of consumer trust on customer satisfaction at the Evan Motor Workshop; there is a positive but not significant effect of consumer trust on consumer loyalty at the Evan Motor Workshop; there is a positive and significant influence of customer satisfaction on consumer loyalty at the Evan Motor Workshop; and there is a positive and significant effect of product completeness on consumer loyalty at the Evan Motor Workshop.